Mysids (Crustacea: Peracarida) from the southern Indian Ocean with descriptions of two new species - Biju, Abraham; Jasmine, Purushothaman; Panampunnayil, Saramma U. (Zootaxa, 2010)
Three species of mysids belonging to two genera from the southern Indian Ocean (Lat. 31–55°S and Long. 45°E) are reported, of these two species - Siriella brevispina and Euchaetomera spinosa - are recorded as new to science. Siriella brevispina shares characters associated with the Brevicaudataand Thompsonii-groups and is distinguished from related species by the presence of a short telson, the anterior margin of the carapace with a triangular rostral plate, the labrum with a long process on the anterior margin, and the inner margin of the uropodal endopod showing an alternating arrangement of long and short spines. Euchaetomera spinosa is distinguished from the morphologically similar species Euchaetomera zurstrasseni by the absence of an ocular papilla, presence of a distal suture in the antennal scale, and the arrangement of spines on the telson.